The Anatomy of Tax Avoidance: Do Related Party Transactions, Inventory Intensity, or Foreign Ownership Play a Role? - Husniatul Qorina; Made Duddy Satyawan (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – Related-party transactions, foreign ownership, and inventory intensity have been examined separately in other sectors. However, the basic materials sector has largely been exclude from studies combining these three factors. Yet this sector, while economically significant, is prone to tax avoidance practices. The urgency of this research lies in identifying specific triggers within the sector, so that tax oversight policies can be more effectively targeted. Methods – Secondary data were collected from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) and company websites for the period 2015–2024. Tax avoidance was proxied by the effective tax rate (ETR). The analysis was conducted using panel data regression (FEM) with Stata 17. Findings – Related-party transactions and inventory intensity are negatively and significantly associated with the ETR, indicating higher levels of tax avoidance. Foreign ownership shows a positive but insignificant trend. The model is statistically valid, but the explained variance of the dependent variable is relatively small, with an R² within of 27.72%. Research implications – Since the sample covers only the raw materials sector, these findings can not be generalized to other sectors. Furthermore, the low R-squared value indicates that there are still many other factors outside the model that influence tax avoidance. Nevertheless, these results can still serve as an initial reference for tax authorities to scrutinize related-party transactions and inventory levels in this sector. Originality – The novelty lies in the simultaneous integration of three variables in the raw materials sector over the 2015–2024, an area that has rarely been studied before. This contribution enriches the empirical evidence. Moving forward, additional variables should be explored given the limited R-squared value.